Zwischen Liebesideal und Realismus Theologische Anthropologie als soziale Ressource bei Reinhold Niebuhr - Bellmann, Tina (Universitätsverlag Göttingen, 2018)
What is there left to say about the human condition after the so-called "end of anthropology"? Never before have conceptions of what it means to be a human being been as diverse and fragmented as in the late modern age - with severe consequences for democratic discourse and liberal, "Western" societies as a whole. Examining the work of American theologian Reinhold Niebuhr (1892-1971), the book presents new insights into the intersection of anthropological thought and ethical orientation. Niebuhr, motivated by his perception of profound political and social crises in "Western" societies, develops an innovative, pragmatic and "realistic" type of theological anthropology. His anthropological approach functions as the basis of a much larger endeavor: rescuing Christianity and democracy itself. Reading Niebuhr today opens up a refreshing perspective on current debates on public theology and the so-called "crisis of democracy". In this context, the book argues, theological anthropology can be reclaimed as an essential social resource: It offers a comprehensive understanding of human nature both at its best and at its worst, providing the indispensable basis for the survival and vitality of democracy.